2018
DOI: 10.1590/2179-8087.035016
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Wood and Charcoal from Eucalyptus clones

Abstract: The characteristics of wood and charcoal depend on the genetic material and the sampling position on the tree trunk. The objective of this study was to evaluate the effect of clone and longitudinal position on the characteristics of wood and charcoal of Eucalyptus grandis x Eucalyptus urophylla. Specimens belonging to I144 and GG100 clones both at seven years of age were felled and mechanically processed for disc removal at different longitudinal positions of 0, 3, 6, 9, 12 and 15 meters from the ground. The w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1
14

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 16 publications
1
3
1
14
Order By: Relevance
“…The minimum and maximum values for volatile materials (83 to 87%) and fixed carbon (12 to 17%) D r a f t were similar to those found by Ignacio et al (2019), who evaluated these variables in several eucalyptus clones (E. grandis, E. saligna, E. dunnii, among others). Silva et al (2018) also found values in this same range for both variables in 7-year-old E. grandis x E. urophylla clones.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The minimum and maximum values for volatile materials (83 to 87%) and fixed carbon (12 to 17%) D r a f t were similar to those found by Ignacio et al (2019), who evaluated these variables in several eucalyptus clones (E. grandis, E. saligna, E. dunnii, among others). Silva et al (2018) also found values in this same range for both variables in 7-year-old E. grandis x E. urophylla clones.…”
Section: Discussionsupporting
confidence: 67%
“…Regarding energy density, Lima et al (2020) found that there was a linear correlation between basic wood density and energy density, showing a strong influence of the first variable on the second. Energy density is an essential guideline for solid fuels, as it represents the amount of energy stored in a given volume (Silva et al 2018;Simetti et al 2018). The highest energy density was observed in the clone 2 (E. cloeziana) in Latossol, which produced more energy per cubic meter of wood.…”
Section: Discussionmentioning
confidence: 99%
“…For energy purposes, specifically for charcoal production, wood basic densities ranging from medium to high (> 0.500 g cm -3 ) are desirable. In this research, T. vulgaris wood showed basic density ranging from 0.443 g cm -3 to 0.529 g cm -3 , superior to those verified by Silva et al (2018) for the woods of two 7-years-old clonal hybrids of E. grandis x E. urophylla (0.440 g cm -3 to 0.500 g cm -3 ).…”
Section: Tachigali Vulgaris Has Appropriate Wood Density For Energy Purposescontrasting
confidence: 51%
“…Because the energy density is directly correlated to the density and calorific value of the material, both wood and charcoal from A. fraxinifolium presented a greater amount of heat in a given volume in relation to E. gummiferum, and also when compared to wood (7.83 to 16.16 GJ/m 3 ) (Jesus et al 2017;Silva et al 2018), and charcoal of the Eucalyptus genus (8.37 to 12.61 GJ/m 3 ) (Protásio et al 2015;Protásio et al 2021).…”
Section: Resultsmentioning
confidence: 99%